2016
DOI: 10.15421/021623
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical parameters in the blood of grass snakes (Natrix natrix) in ecosystems under varying degrees of anthropogenic influence

Abstract: The grass snake Natrix natrix (Linnaeus, 1758) is a partly hygrophilous species, distributed throughoutUkraine. This snake may be considered as a test object for environmental biomonitoring. Modern biochemical methods make it possible to obtain new scientific data on the effects of anthropogenic pressure on reptiles. Blood is a sensitive and informative indicator of the condition of an organism as it responds quickly to most changes in exogenous and endogenous factors, and reflects negative influences on both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Dice snake, as opposed to the sympatric grass snake Natrix natrix, occupies the smallscale areas within a certain water body and therefore may fully characterize the environmental conditions of the studied biotope (Bulakhov et al, 2007;Gasso, 2011). Previous research demonstrated unstable biochemical alterations in reptile blood under influence of pollution in the region (Klymenko & Gasso, 2009;Gasso et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dice snake, as opposed to the sympatric grass snake Natrix natrix, occupies the smallscale areas within a certain water body and therefore may fully characterize the environmental conditions of the studied biotope (Bulakhov et al, 2007;Gasso, 2011). Previous research demonstrated unstable biochemical alterations in reptile blood under influence of pollution in the region (Klymenko & Gasso, 2009;Gasso et al, 2016).…”
Section: Introductionmentioning
confidence: 99%